Formwork Construction system in Kuwait - Anwar Abdullah Jdaie Alghanim (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2019)
This study aimed to evaluate the differences between steel and timber formwork regarding cost, quality, and time of completion of building construction projects in Kuwait. Forty projects were selected to represent the construction business in the country. The study method was based on survey data collection (questionnaires, interview, and observation). The findings of the study showed that the contractors prefer to buy steel formwork than timber formwork system, although timber formwork is cheaper than steel formwork. Also the study found that the field of steel formwork reached a mean of (4.425), which puts steel formwork in first rank.